A Comprehensive Phylogenetic Analysis of the MAP4K Family in the Green Lineage - Pan, Lixia; Fonseca De Lima, Cassio Flavio; Vu, Lam Dai; De Smet, Ive (Frontiers in Plant Science, 2021)
The kinase-mediated phosphorylation impacts every basic cellular process. While mitogen-activated protein kinase technology kinase kinases (MAP4Ks) are evolutionarily conserved, there is no comprehensive overview of the MAP4K family in the green lineage (Viridiplantae). In this study, we identified putative MAP4K members from representative species of the two core groups in the green lineage: Chlorophyta, which is a diverse group of green algae, and Streptophyta, which is mostly freshwater green algae and land plants. From that, we inferred the evolutionary relationships of MAP4K proteins through a phylogenetic reconstruction. Furthermore, we provided a classification of the MAP4Ks in the green lineage into three distinct.